ANALISIS POTENSI EKONOMI DAERAH DALAM RANGKA PENGEMBANGAN KOMODITAS UNGGULAN UMKM DI WILAYAH KABUPATEN CIREBON, JAWA BARAT - HASANUDDIN, TUBAGUS (Indonesian Journal of Socio Economics)
This research was aim to know Â the special quality UMKMâs comodity in Cirebon, West Java.The research was conducted using survey method and the samples were 105 responden. The respondents were selected using purposive random sampling, This research started from September 2007 until the November 2007. The data collected were analyzed with sectoral qualitative anlysis method. The resultÂ  of the research showed that, the special quality comodities in Cirebon are sugar reed, shrimp, rattan, rice, belinjo, and batik. The aspects that very influential to themÂ  are modal, production process and government capability.